Systematic review on knowledge and awareness of breast cancer and risk factors among young women - Hamdan Almutairi, Aeshah; Md Tamrin, Shamsul Bahri; Wirza, Rahmita; Ahmad, Norliza (Australian International Academic Centre, 2019)
Introduction: Breast cancer is considered the primary cancer to affect women according to the global context. Due to its crucial escalation, it has become vital to inform the general population regarding breast cancer symptoms, risk factors and earlier detection methods. The main aim of the present study is to conduct a systematic review of breast cancer and the risk factors affecting young adult women. Methods: A systematic literature review was carried out to garner global studies on breast cancer risk factors as well as to understand the degree to which breast cancer and its associated risk factors are understood. The primary study included the exploration of databases and journal websites, PubMed, Google Scholar and Medline. The articles studied for the review was focused on the printed original English articles from the year 2008 to December, 2017. This review highlights the necessity for further studies regarding knowledge of breast cancer and its risk factors among young adult women are understood. Conclusion: Knowledge about breast cancer and its risk factors among young women was inadequate. Furthermore, cultural sensitivities should be adjusted to ensure optimal awareness among the public, in particular teenagers and young adult women. Intensive educational campaigns should be planned to increase breast cancer awareness in order to minimize the observed deficit of knowledge. The role of prevention and procedures to screen breast examinations in clinics as well as mammography should all be highlighted in order to achieve these goals and obtain the required data.